2020
DOI: 10.25035/jade.02.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Identity: Complexity of the “Iceberg”

Abstract: Athletic identity is a common topic in research on athlete experiences and development. Many researchers rely on the understanding of athletic identity as conceptualized by Brewer, Van Raalte, and Linder (1993). This seminal work provided a foundational understanding for conducting survey research on athletic identity. However, the emphasis on survey approaches has resulted in an incomplete understanding of athletic identity as deeper meanings of the construct are taken for granted (Ronkainen, Kavoura, & Ryba,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Association of athletic identity and race or ethnicity in the youth population is also poorly defined, though Anderson et al and others suggest that Hispanic and minority youths perceive themselves as having lower athletic identity ( Anderson et al, 2009 , 2011 ; Edison et al, 2021 ). Youth athletes appear to conflate athletic identity and personality as they mature ( Von Rosen et al, 2018 ; Newton et al, 2020 ; Edison et al, 2021 ), though athletic identity may begin to decrease with age at the undergraduate level ( Renton et al, 2021 ). The convergence of athletic identity and personality in youth may prove problematic if their athletic identity is interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Association of athletic identity and race or ethnicity in the youth population is also poorly defined, though Anderson et al and others suggest that Hispanic and minority youths perceive themselves as having lower athletic identity ( Anderson et al, 2009 , 2011 ; Edison et al, 2021 ). Youth athletes appear to conflate athletic identity and personality as they mature ( Von Rosen et al, 2018 ; Newton et al, 2020 ; Edison et al, 2021 ), though athletic identity may begin to decrease with age at the undergraduate level ( Renton et al, 2021 ). The convergence of athletic identity and personality in youth may prove problematic if their athletic identity is interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, instead of identity transition, it is possible that these athletes struggled to pursue new avenues ( Podlog et al, 2011 ; Von Rosen et al, 2018 ) and found difficulty replacing that aspect of their identity. Regardless, results emphasize that a youth’s athletic identity is vulnerable in times of situational change such as injury, and an adequate support system is essential, as such ( Newton et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To better gauge an athlete’s outcomes in return-to-sport, an understanding of a child’s dependence on and involvement in sport—their athletic identity—may be helpful. Athletes may be forced to alter or abandon their athletic identity during periods of situational change, such as injury and retirement from sport ( Brewer and Cornelius, 2010 ; Newton et al, 2020 ). In fact, injury is a major cause of early retirement at all ages ( Ardern et al, 2014 ; McKay et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Collegiate athletes often live in a hyphenated world wherein each waking moment they are expected to be (and are viewed as) one of multiple identities (Kidd et al, 2018;Newton et al, 2020). Most notably, collegiate athletes often harbor identities that are shaped around their dual roles as a student and an athlete (Sturm et al, 2011).…”
Section: The Life Of Collegiate Athletesmentioning
confidence: 99%
“…While there is inconsistency in the literature as to whether these identities operate independently (Sturm et al, 2011;van Rens et al, 2019;Yukhymenko-Lescroart, 2018), it is known, unsurprisingly, that academic identity is positively associated with academic performance (Guay et al, 2004). On the other hand, a parsimonious definition of athletic identity states that it is the extent to which one embraces the role of an athlete (Newton et al, 2020;Pack et al, 2017). Similar to academic identity, the stronger athletic identity one possesses, the stronger subsequent athletic performances one experiences (van Rens et al, 2019) -most likely due to the increasing commitment and effort expended on these activities.…”
Section: Identities Of Collegiate Athletesmentioning
confidence: 99%